2012
DOI: 10.1152/ajpgi.00440.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanism of mechanotranscription in colonic smooth muscle cells

Abstract: Mechanical stretch in obstruction induces expression of cyclooxygenase-2 (COX-2) in gut smooth muscle cells (SMCs). The stretch-induced COX-2 plays a critical role in motility dysfunction in obstructive bowel disorders (OBDs). The aims of the present study were to investigate the intracellular mechanism of mechanotranscription of COX-2 in colonic SMCs and to determine whether inhibition of mechanotranscription has therapeutic benefits in OBDs. Static stretch was mimicked in vitro in primary culture of rat colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(81 citation statements)
references
References 42 publications
5
76
0
Order By: Relevance
“…Consistent with previous findings 1,29,30 , colonic smooth muscle contractile response was dramatically suppressed in OB. However, antibiotic treatment did not improve colon muscle contractility in OB (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with previous findings 1,29,30 , colonic smooth muscle contractile response was dramatically suppressed in OB. However, antibiotic treatment did not improve colon muscle contractility in OB (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The serosa and mucosa were removed and the remaining muscularis was cut into pieces [15]. The tissue was placed in a centrifuge tube containing a tissue digestion mixture of 0.1% collagenase type II (GIBCO) and 0.01% soybean trypsin inhibitor in Dulbecco's modified Eagle's medium (DMEM, GIBCO) for 20 min at 37°C [16], centrifuged for 5 min, and then the supernatant was removed. The cell pellet obtained was resuspended and stored at 37°C in DMEM containing 100 U/ml penicillin, 100 μg/ml streptomycin (P/S), and 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, MCP-1 is a potent chemoattractant with an action of recruiting lymphocytes, monocytes and other inflammatory cells into the local site of the gut wall [2], [46], [47]. Our previous studies demonstrated that gene expression of COX-2 is markedly induced by mechanical stress in gut smooth muscle cells [25], [30]. COX-2 –derived PGs (i.e.…”
Section: Discussionmentioning
confidence: 99%